Perencanaan Sistem Informasi Pelaporan Kasus Kekerasan Berbasis Constraint: Studi pada Yayasan Sanggar Suara Perempuan - Jeny Maryana Nuban; Eko Sediyono; Evi Maria (Institut Teknologi Garut, 2026)
Violence case reporting systems in community-based organizations are often framed as technical solutions, overlooking the social and operational conditions that shape their use. This study examines how reporting system requirements are formed in such contexts and develops an information system design that responds to these conditions. The study draws on a qualitative, design-oriented case study conducted at Yayasan Sanggar Suara Perempuan (SSP). Data were collected through interviews and observations with key informants, analyzed thematically, and mapped onto the Ward and Peppard framework to inform system design. The findings show that system requirements are not purely functional but emerge as a configuration of interacting constraints, process fragmentation, data security risks, and social barriers that simultaneously bound integration, visibility, and user access. Fragmented reporting practices across unintegrated channels lead to data inconsistencies and delays, while concerns about identity exposure constrain user participation. In response, the study proposes an integrated reporting system featuring centralized data management, anonymous reporting, and role-based access control. These findings demonstrate that system design in high-risk, socially sensitive contexts cannot be derived from functional requirements alone but must be configured within a constraint-bounded design space that directly shapes and limits design decisions.